2021
DOI: 10.1159/000518362
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Anti-GBM Antibodies in Diagnosing Anti-Glomerular Basement Membrane Disease: A Systematic Review and Meta-Analysis

Abstract: <b><i>Background:</i></b> The sensitivity and specificity of anti-glomerular basement membrane (GBM) antibodies have not been systematically analyzed. In this systematic review, we aimed to evaluate the diagnostic accuracy of anti-GBM antibodies for anti-GBM disease. <b><i>Summary:</i></b> Potential studies were searched using MEDLINE, Embase, the Cochrane Library, and the International Clinical Trials Registry Platform based on the index test and target conditio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 30 publications
0
5
0
1
Order By: Relevance
“…10 A systematic review and meta-analysis reported that the sensitivity and specificity of anti-GBM antibody detection in diagnosing anti-GBM disease were 93% and 97%, respectively. 11 In another study, Qu et al 12 claimed that IgG deposition was detected among all patients with anti-GBM disease. Large biopsy series suggest that 95% of patients will have evidence of crescent formation on kidney biopsy, and that in 80% of patients >50% of glomeruli will be affected.…”
Section: Discussionmentioning
confidence: 97%
“…10 A systematic review and meta-analysis reported that the sensitivity and specificity of anti-GBM antibody detection in diagnosing anti-GBM disease were 93% and 97%, respectively. 11 In another study, Qu et al 12 claimed that IgG deposition was detected among all patients with anti-GBM disease. Large biopsy series suggest that 95% of patients will have evidence of crescent formation on kidney biopsy, and that in 80% of patients >50% of glomeruli will be affected.…”
Section: Discussionmentioning
confidence: 97%
“…Due to the retrospective character of this study, no further investigations about clinical and serological manifestations in these patients are feasible. Future studies could provide further insights and moreover address the need for comparisons among different immunoassays ( 8 ). In addition, limitations of the present study could be addressed, for example with regard to sample selection.…”
Section: Discussionmentioning
confidence: 99%
“…In routine diagnostics, this antigen is thus utilized as substrate by various immunoassay formats, most notably indirect immunofluorescence tests and ELISA, for the detection of anti-GBM autoantibodies to support diagnosis of anti-GBM disease. A recent literature-based meta-analysis confirmed the potential high sensitivity and specificity in the diagnosis of anti-GBM disease ( 8 ).…”
Section: Introductionmentioning
confidence: 86%
“…The pathogenic anti-GBM antibodies are usually IgG class, but a few cases are caused by IgA or IgG4 alone [ 5 , 6 ]. The sensitivity and specificity of anti-GBM antibodies were 93% and 97%, so they showed low false-negative and high true positive rate [ 7 ]. At another point of view, 32% of all anti-GBM positive samples have detectable ANCA, and 5% of all ANCA-positive serum samples also have detectable anti-GBM antibodies, but the mechanism is unclarified [ 8 ].…”
Section: Discussionmentioning
confidence: 99%